2013
DOI: 10.1111/ene.12080
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous immunoglobulin in responders to intravenous therapy with chronic inflammatory demyelinating polyradiculoneuropathy

Abstract: SCIG treatment in CIDP is feasible, safe and effective, and seems an attractive alternative to IVIG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 27 publications
7
130
3
3
Order By: Relevance
“…Toxicity and tolerability have been tested and the use has been approved by the FDA. s.c. IgG has been shown to be safe in individuals with immunological neurological diseases like multifocal motor neuropathy and chronic inflammatory demyelinating polyneuropathy [8,9,10]. Although the number of the cases is small, this therapy is well tolerated and the reports suggest a good response to s.c. IgG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity and tolerability have been tested and the use has been approved by the FDA. s.c. IgG has been shown to be safe in individuals with immunological neurological diseases like multifocal motor neuropathy and chronic inflammatory demyelinating polyneuropathy [8,9,10]. Although the number of the cases is small, this therapy is well tolerated and the reports suggest a good response to s.c. IgG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Isokinetic testing protocols, described by Harbo et al 39 have been used as an outcome measure in studies exploring the safety and efficacy of subcutaneous administration of immumoglobulins in CIDP. [40][41][42] Cost and space constraints limit the utility of isokinetic dynamometry in the routine clinical care setting. The assessment also can be timely to perform and requires expertise on the part of the evaluator to become familiar with the testing protocols.…”
Section: Manual Muscle Strength Testing and Isokinetic Strength Testingmentioning
confidence: 99%
“…The consequence is a higher and more stable IgG level, which may prevent end-of-dose reduction in efficacy and minimize side effects [51]. A double-blind, placebo-controlled RCT of SCIG, performed in 30 patients with CIDP who were previously responders to IVIG, showed that there was no significant difference in Medical Research Council (MRC) sum score or grip dynamometry, but there was a significant improvement in isokinetic muscle strength in SCIG-treated patients [52]. Moreover, 70 % of patients preferred SCIG administration.…”
Section: Ivigmentioning
confidence: 99%